Society Security Vulnerability In Indonesia-Malaysia Border, Sajingan Besar District, Sambas Regency - Ningtias, Kartika; Sudagung, Adityo Darmawan; Darajati, Muhammad Rafi (Indonesian Journal of International Law, 2018)
This research is intended to examine the means of Indonesia in addressing the vulnerability of the societal security in the Indonesia-Malaysia border area at Sajingan Besar District, Sambas Regency. Transnational activities in the Indonesia-Malaysia border area, especially at Sajingan Besar District, Sambas Regency, had an impact on national security. The existence of Indonesian society was threatened because of the very intense transnational activities with the Malaysian people on the border area. State as an actor in international relations has the obligation to secure its territory and inhabitants. The method used in this research was qualitative research method with case study technique. Data were collected by conducting interviews and conducting secondary data tracking, either from books, journals, or internet sources. The study was conducted by analyzing the societal security and national security approach. The means of Indonesia in 2014-2016 to address the vulnerability in Sajingan Besar District area include several issues, such as mentioned “border area” in Nawacita, increasing presidential visits to the border area, development and improvement of infrastructure, and improvement of public policy. The means that had been done shows the increased attention and real action from the government of Indonesia towards their border area